Persepsi Petani Terhadap Sistem Integrasi Sapi -Kelapa Sawit (Studi Kasus Petani Plasma PT. Citra Nusa Inti Sawit Di Kecamatan Mukok Kabupaten Sanggau) - Komariyati, Abang Muhammad Ali, Ani Muani, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
Cattle Systems Integration - Palm Oil (SISKA) is the union of plantation business in the cultivation of beef cattle in oil palm plantations. The purpose of the study are to obtain the farmer's perception on the cattle – palm oil integration system in District Mukok and to determine the relationship between internal and external factors and the farmers perception on the cattle – palm oil integration systems. The survey method applied to collect empirical data based on interviews and observations. The data consists of primary data and secondary data. The study population numbered 183 farmers, the sample then determined by the formula slovin are 126 farmers. Analysis of the data used is descriptive analysis and the average score and Spearman rank correlation using SPSS 22. The results showed farmers perception on cattle - palm oil integration system in District Mukok in sufficient category. There was a significant relationship between farmer’s internal and external factors with farmer’s perceptions on the cattle-palm integration system in District Mukok.Factors that influence the farmers' perceptions of internal and external factors are the age of the farmer, formal education, farming experience, the frequency of obtaining counseling, frequency of training, parties that support, the frequency of assistance, the level of knowledge and economic benefits frequency of receiving information.Keywords: Perception, SISKA, Smallholder PT. Citra Nusa Kernel Oil.